TIME MANAGEMENT AND ACADEMIC ACHIEVEMENT AMONG UNIVERSITY STUDENTS: THE MODERATING ROLE OF THE LEARNING ENVIRONMENT - Nurul Khoerunisa; Karina Zian Rehmania; Idam Wahyudi; Anggun Sulistyowati (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study examines the influence of time management on academic achievement among university students and investigates the moderating role of the learning environment in this relationship. Although effective time management is widely recognized as an essential component of self-regulated learning, students’ academic performance is not solely determined by their individual abilities. Still, it is also shaped by contextual factors surrounding their learning experiences. Using a quantitative approach, data were collected from 100 undergraduate students selected via purposive sampling and analyzed using Structural Equation Modeling in SmartPLS 4. The results indicate that time management has a significant positive effect on academic achievement, suggesting that students who can organize their study schedules, prioritize tasks, and manage deadlines tend to achieve better academic outcomes. However, the learning environment was found to negatively moderate this relationship, meaning that in certain learning conditions, such as noisy spaces, limited academic support, or poorly structured learning activities, the positive influence of time management may weaken. These findings highlight the complex interplay between individual skills and environmental factors in shaping academic performance. The study contributes to the literature by integrating human resource management (HRM) perspectives with educational psychology, emphasizing that academic success requires both personal competencies and institutional support. In practice, the results underscore the importance of universities in providing conducive learning environments while implementing programs that strengthen students’ time management skills. Recommendations for future research include using larger samples, adopting multi-institutional designs, and exploring additional moderating factors, such as motivation, mental well-being, and digital learning engagement.